Staphylococcus aureus Resistance to Several Antibiotics Isolated from Broiler Chicken Meat at the Traditional Market in Banda Aceh-Indonesia - Rastina; M Daud AK; Denny I Hasan; Rosmaidar; Indah Mulya; Meli Br Sembiring Meliala; Bilqis Rizki Ilahi (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2024)
Staphylococcus aureus is a prevalent pathogen that frequently infects broiler chickens, with treatment typically involving the use of antibiotics. Antibiotic resistance refers to the ability of bacteria to withstand the effects of these drugs. This study aims to assess the prevalence of antibiotic-resistant S. aureus in broiler chicken meat sold at Traditional Market in Banda Aceh City. Employing a cross-sectional study, samples were collected through purposive sampling. A total of 100 breast meat samples from broiler chickens sourced from traditional markets in Banda Aceh City were analyzed. The antibiotics tested in this study included ampicillin, streptomycin, ciprofloxacin, and erythromycin. All positive isolates of S. aureus underwent MRSA testing. Data were analyzed descriptively. The findings reveal that out of the 100 samples, 10 tested positives for Staphylococcus aureus. Of these, four samples exhibited resistance to erythromycin (40%), two samples were resistant to ampicillin (20%), and one sample showed resistance to streptomycin (10%), while all ten samples were sensitive to ciprofloxacin (100%). Out of the 10 MRSA isolates analyzed, the mecA gene was detected in one isolate. Consequently, it can be concluded that broiler chicken meat sold in traditional markets in Banda Aceh City demonstrates varying levels of resistance to several antibiotics.